Life Cycle Assessment Study May Exclude Less Significant Processes from the Scope—Reply to Comment by Heijungs and Cucurachi - Andrzej Marcinkowski; Joanna Kopania (Energies, 2021)
In the comment of Heijungs and Cucurachi [...]